2016
DOI: 10.1051/bioconf/20160702029
|View full text |Cite
|
Sign up to set email alerts
|

Change in Kinetic parameters of commercial yeast in the presence of copper fungicides

Abstract: Abstract. The Serra Gaucha has a high rainfall occurrence during the ripening and harvest. It results in higher use of fungicides, being the copper-based ones, the most commonly used. High levels of this metal can cause stress to the yeast, thus, influencing on the fermentation kinetics. The aim of this study was to evaluate the fermentative behavior of oenological yeast in the presence of copper content in the must. The experiment used the following fungicides: Copper Sulfate, Copper Oxychloride and Copper Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
3
1
0
Order By: Relevance
“…However, most M. pulcherrima strains isolated from wineries tolerated up to 2 mM copper (Barbosa et al 2018 ) and high resistance to copper up to 10 mM was reported for Starmerella bacillaris and Metschnikowia yeasts isolated from high-sugar habitats (Binati et al 2019 ). The low copper tolerance of T. delbrueckii strains demonstrated in this study is in accordance with data reported by Gava et al ( 2016 ).…”
Section: Resultssupporting
confidence: 93%
“…However, most M. pulcherrima strains isolated from wineries tolerated up to 2 mM copper (Barbosa et al 2018 ) and high resistance to copper up to 10 mM was reported for Starmerella bacillaris and Metschnikowia yeasts isolated from high-sugar habitats (Binati et al 2019 ). The low copper tolerance of T. delbrueckii strains demonstrated in this study is in accordance with data reported by Gava et al ( 2016 ).…”
Section: Resultssupporting
confidence: 93%
“…For both varieties, the different copper conditions led to fermentations with identical overall behavior. These results are in accordance with published results ( Gava et al, 2016 ) where the fermentation parameters of strain X5 were unaffected by copper concentration and formulation with the exception of a slightly longer lag phase for copper oxychloride (23.40 h) compared to copper hydroxide (22.44 h), while copper sulfate was intermediate (23.03 h). For other strains such as Anaferm Riesling, fermentation parameters remained unchanged up to 25 mg/l of copper while Oenoferm X-trem showed slower fermentation from 10 mg/l upwards.…”
Section: Resultssupporting
confidence: 93%
“…For both varieties, the different copper conditions led to fermentations with identical overall behavior. These results are in accordance with published results (Gava et al, 2016) where the fermentation For other strains such as Anaferm Riesling, fermentation parameters remained unchanged up to 25 mg/l of copper while Oenoferm X-trem showed slower fermentation from 10 mg/l upwards. Other works have reported that fermentation kinetics were differently affected at 15 mg/l of copper (Ferreira et al, 2006), suggesting that yeast strain was the most important factor in copper resistance, as reported later (Capece et al, 2016(Capece et al, , 2017.…”
Section: Monitoring Of Fermentations Under Copper Stresssupporting
confidence: 93%
“…Consequently, the selection of resistant strains is crucial as there is a risk of high levels of copper residues in grape-must [61]. Herein, all isolates tolerated the maximum concentration of copper sulfate tested (2 mM), except two isolates (Mp3 and Mp64).…”
Section: Phenotypic Characterizationmentioning
confidence: 92%